(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes, from a philosophical perspective, the impact of artificial intelligence on social stability, as well as the issues of information manipulation and media literacy. In the context of the digital society, it examines the rapid increase in information flows, the influence of artificial intelligence technologies on human consciousness and value orientations, and the necessity of developing media literacy on a scientific basis.